2020
DOI: 10.1371/journal.pntd.0008825
|View full text |Cite
|
Sign up to set email alerts
|

Community perspectives on scabies, impetigo and mass drug administration in Fiji: A qualitative study

Abstract: Scabies is endemic in Fiji and is a significant cause of morbidity. Little is known about the sociocultural beliefs and practices that affect the occurrence of scabies and impetigo, or community attitudes towards the strategy of mass drug administration that is emerging as a public health option for scabies and impetigo control in Fiji and other countries. Data were collected during semi-structured interviews with 33 community members in four locations in Fiji’s Northern Division. Thematic analysis examined pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“… 4 Scabies may impact a person in a number of ways: the intense itch can affect sleep and concentration at school or work and the appearance of lesions and the highly infectious nature of the disease can lead to stigma. 5 Secondary complications can result in hospitalisation, cause long-term disability and may even be fatal. 1 Four previous studies have investigated health-related quality of life (HRQoL) impacts in individuals with scabies.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Scabies may impact a person in a number of ways: the intense itch can affect sleep and concentration at school or work and the appearance of lesions and the highly infectious nature of the disease can lead to stigma. 5 Secondary complications can result in hospitalisation, cause long-term disability and may even be fatal. 1 Four previous studies have investigated health-related quality of life (HRQoL) impacts in individuals with scabies.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty papers reported on community perceptions, and 15 papers reported on stakeholder perceptions. Regarding study design, 11 papers reported on mixed methods studies, 11 papers reported on qualitative study designs, one paper reported on a Papers reporting on studies from India [14,[40][41][42][43][44][45][46][47][48][49], Indonesia [50][51][52], Philippines [15,[53][54][55], Bangladesh [19,56], Laos [57], American Samoa [18], Papua New Guinea [58] and Fiji [25].…”
Section: Resultsmentioning
confidence: 99%
“…These included one mixed methods study and two qualitative studies in the Philippines [53][54][55]; two mixed methods studies in Bangladesh [19,56]; one qualitative study in India [49]; and one rapid ethnography in Laos [57]. One qualitative study focused on scabies in Fiji [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 , 8 Furthermore, poor sleep, poor school engagement, social stigma and school days lost due to infestation are psychosocial implications that may be deprioritized in the context of managing the acute infestation. 9 , 10 The cost and accessibility of treatment along with primordial factors, including overcrowding, are issues in some communities. 11 Successful treatment for children with scabies requires synchronous environmental and pharmacological management.…”
Section: Introductionmentioning
confidence: 99%